Studying of antimicrobic activity of phytoextracts and biocomposites (Eurasian Journal of Ecology, 2016)
Phytoextract and heterogeneous active biocomposites enriched with it on the basis of CRH were received in this work. Antimicrobic properties of phytoextracts and biocomposites concerning the causative agent ofpyoinflammatory processes - Staphylococcus aureus 209 were studied in vitro.
Keywords: phytoextracts; biocomposites; herbs; antimicrobic property; sorbent; functionalization